Effect of Time and Temperature Variables on Prothrombin Time and International Normalized Ratio of Plasma in Patients in Gampaha, Sri Lanka - Vıraj Ranasınghe; Sameera Maduranga Jayasundara; Sanjaya De Sılva; Faiz Marikar; Randıka Wımalasırı Yapa (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Generating accurate results for Prothrombin time (PT) and International Normalized Ratio (INR), PT/INR test is paramount in treatment monitoring. The diagnosis process measures how long it takes blood to clot. The main objective of this study was to determine the effect of storage time and temperature variables on PT and INR results in patients attending Hematologic clinics in Sri Lanka. This cross-sectional study was conducted during June and July 2021. PT was measured in the plasma samples, stored at different temperatures at baseline (0 hours), and then after 12 hours, 18 hours, and 24 hours after specimen collection. INR was calculated from each result, and the deviation percentage of PT and INR was calculated compared to the baseline result (0 hours). Then PT and INR percentage deviation is grouped as <10% and >10% to find biologically significant variations while paired t-test was performed to find statistical significance using GraphPad prism 8.4.3. At refrigerated temperature, both PT and INR results showed>10% variation once kept 24 hours, and this variation was statistically significant (p<0.01, Wilcoxon matched paired sign ranked test). The plasma specimens kept at laboratory temperature and specimen collection room temperature for 18 hours indicated >10% variation of PT and INR values, while these variations were significant at the same criteria above. These results suggest that the separated plasma could only be recommended to test up to 12 hours. Therefore, the laboratories that operate in the same climatic conditions can now use these results to plan the specimen collection accordingly.